Organisational support in knowledge transfer activities towards ERP success scale development and validation - Muallah, Nur Izzah; A. H., Nor Aziati (Academic Research Publishing Group, 2018)
The successes of ERP system in an organization depend on knowledge transfer activities being made and the effectiveness of the transferred knowledge between the parties involved. It is important to determine a set of knowledge transfer activities that need to be done besides efforts undertaken by the organisation in ensuring ERP success. Currently, there is still lacking of standard knowledge transfer measurement and organisational support that impacted ERP system. Previous research has reported various factor impacted the transfer of knowledge in strategic alliances and joint venture. Nonetheless, organisational support is the least factor mentioned especially studies from Malaysia. Addresses this gap, the main purpose of this study is to develop a validated scale of organisational support in supporting knowledge transfer activities towards ERP system success. The study has adapted six stages of scale development and validation of measurement items according to legitimate measures. The measurement scales formed are based on literature review and field studies conducted to increase the reliability and validity values. Organisational support constructs were divided into Top Management Support, Communication and User Training and Education. Total of 16 items have been successfully established for further validation.